Assessing adolescent preference in the treatment of first‐episode psychosis and psychosis risk. Issue 3 (19th July 2013) - Welsh, Patrick; Tiffin, Paul A.
Abstract Aim The objective of this study was to investigate the treatment preferences of adolescents with a first‐episode psychosis (FEP) or at‐risk mental state (ARMS) for psychosis. Methods A questionnaire was distributed to all adolescents (12–18 years) within an early intervention in psychosis service based in North‐East England, during a 3‐month period. Results Forty eligible young people responded (53% response rate). The majority of FEP and ARMS participants endorsed psychoeducational material as the most popular treatment choice (36/40; 90%) from the interventions described. Participants with FEP indicated a significant preference for using antipsychotic medications over their ARMS counterparts (75% vs. 25%). Conclusions These findings support the use of psychoeducational interventions (both groups) and antipsychotic medication in adolescent FEP (as opposed to ARMS) patient groups, albeit in a small sample requiring replication. This study indicates that the generation of future treatment guidelines and the allocation of clinical resources should be informed by patient preference where possible.